KEARIFAN LOKAL DALAM PRAKTIK JUAL BELI KOPI PERSPEKTIF EKONOMI SYARIAH DI DESA TAPAK GEDUNG KABUPATEN KEPAHIANG - Firda Iksan; Nilda Susilawati; Makmur (JSE: Jurnal Sharia Economica, 2026)
This study aims to analyze the implementation of local wisdom in the practice of coffee trading and examine its conformity with Islamic economic principles in Tapak Gedung Village, Kepahiang Regency. Coffee is the primary commodity supporting the community's economy, where trading practices have been carried out traditionally from generation to generation. The research employed a qualitative field research approach using observation, interviews, and documentation techniques. Informants consisted of coffee farmers, collectors, religious leaders, and village officials who understood the coffee trading mechanism. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings indicate that coffee trading practices are strongly influenced by local wisdom values such as trust, kinship, and long-term social relationships. However, several practices still indicate elements of uncertainty in determining quality, prices, and payment systems that have not fully complied with Islamic economic principles, particularly regarding transparency and fairness. Nevertheless, the local wisdom maintained by the community also contributes positively to sustaining harmonious social relations among market participants. Therefore, strengthening public understanding of Islamic business ethics is necessary so that local wisdom can continue to develop without contradicting Islamic legal principles.